From conceptual diagrams to semi-quantitative models of social-ecological systems: exploring fuzzy cognitive mapping for a coastal fisheries system in the Southern Cape, South Africa - Le Roux, Natalie Anne (Department of Biological Sciences, 2025)
The world's oceans face growing threats, necessitating immediate and sustainable action. Disadvantaged coastal communities are especially vulnerable to global change and ongoing human pressures. Strengthening the resilience and adaptability of marine social-ecological systems is crucial for achieving long-term conservation success, necessitating systems-based, inclusive, and communicable approaches. Qualitative modelling, particularly fuzzy-logic cognitive mapping (FCM), offers a promising toolset in support of strategic decision-making. This study builds on causal maps co-created with small-scale fishers from South Africa's southern Cape, integrating expert views and local knowledge through the use of FCM and a rapid prototyping approach. Iterative FCM application involved testing software suitability, refining prototypes, and co-creating scenarios to simulate outcomes and understand key drivers of change. Modifications to the ‘fcm' RStudio package addressed a critical limitation, enhancing the tool's capacity to analyse diverse scenarios effectively and reliably. Findings highlight the significant vulnerabilities of small-scale fishing communities in the southern Cape, driven by economic, policy, and environmental stressors. The study highlights the importance of participatory approaches in identifying vulnerability drivers and enhancing understanding of system dynamics. By integrating local knowledge with FCM, this research advances tools for exploring resilience and vulnerability in these communities.